PROJECT-BASED LEARNING AND RALLY TABLE: EFFECTS ON ELECTRICITY LEARNING OUTCOMES IN HIGH SCHOOL - Naura, Aqilah; Syahfirra, Gaurin Rani Masyitha; Rohmiati, Dyah Palupi; Ramadhan, Firdausi (Center for Research and Publication Universitas Islam Negeri (UIN) of Ar-Raniry, 2025)
The implementation of Project-Based Learning (PjBL) in physics instruction is aligned with topics that have direct applications in daily life, such as electricity. One of the projects that students can undertake is constructing a simple household electrical installation. However, PjBL has a limitation in which students only focus on the final product of the project rather than the underlying concepts required to complete it. This condition leads to decreased student engagement during the learning process, which in turn may increase the probability of a decline in learning outcomes. This weakness can be addressed by integrating the Rally Table learning strategy. Therefore, this study aims to measure the effectiveness of PjBL combined with Rally Table in improving the learning outcomes of 12th-grade students on the topic of electricity. The study employed a one-group pretest–posttest design with a sample of 72 students. The findings indicate an improvement in learning outcomes by 37%. In addition, classroom observations revealed that proper time allocation between regular learning activities and project work is essential to foster active student engagement throughout the learning process.